“Allowing Yourself to Sexual Freedom”: Making Sense of Sexual Spontaneity with Disability - Dune, Tinashe; Mpofu, Elias (Advances in Social Sciences Research Journal, 2015)
Constructions of sexuality and disability have been discussed widely by scholars across a number of fields. However, there has been relatively little research on how people with cerebral palsy construct their own sexuality and the salience of the socio-sexual schema which are involved in this process. One such sexual schema is that of sexual spontaneity. This research explored how people with cerebral palsy construct sexual participation particularly in relation to sexual spontaneity and the role it played in how they described their sexuality. This project utilized a hermeneutic phenomenological approach to explore these questions. Seven in-depth, semi-structured interviews were conducted with five men and two women with moderate to severe cerebral palsy. Sexual spontaneity was primarily a derivative of sexual exploration. Furthermore, participants defined sexual spontaneity as liberating and allowed them to experience their sexuality with others relatively independent of normative sexual scripts. Participants also described their sexuality primarily in terms of major transitions and experiences which involved others. The findings emphasize that people with cerebral palsy are cognizant and intelligent agents in the construction of their sexuality. Their articulations, understandings and descriptions of their sexuality demonstrate their interest and awareness in their sexuality and issues related to it.